The Legal Consequences of Credit Guarantee by Banks to Third Parties - Al Rasyid, Abdillah Salim (Jurnal Konstatering, 2022)
Research with the title "Legal Consequences of Credit Guarantees by Banks to Third Parties" examines legal issues that arise in credit agreements, especially with motorized vehicle guarantees at Bank Lampung, West Lampung branch, where collateral is not placed on the creditor but on the debtor, the guarantee given to the creditor is only the BPKB of the car while the car unit remains with the debtor, so that in this case the debtor pawns the car as the object of collateral to a third party. The approach method used in this study is sociological juridical, meaning that research is carried out on the real conditions of the application of law to society with the aim and objective of finding facts (fact-finding), which then leads to identification (problem identification) and then leads to problem solving (problem solutions). The default on credit while the solution to these legal problems is (i) Obliging the debtor to provide a replacement guarantee that is equivalent in value. (ii) Obliging debtors to repay their debts.Keywords: Bank; Consequences; Guarantee.